Ilheus virus isolation in the Pantanal, west-central Brazil. - Alex Pauvolid-Corrêa; Joan L Kenney; Dinair Couto-Lima; Zilca M S Campos; Hermann G Schatzmayr; Rita M R Nogueira; Aaron C Brault; Nicholas Komar (Public Library of Science (PLoS), 2013)
The wetlands of the Brazilian Pantanal host large concentrations of diverse wildlife species and hematophagous arthropods, conditions that favor the circulation of zoonotic arboviruses. A recent study from the Nhecolândia sub-region of Pantanal reported serological evidence of various flaviviruses, including West Nile virus and Ilheus virus (ILHV). According to the age of seropositive horses, at least three flaviviruses, including ILHV, circulated in the Brazilian Pantanal between 2005 and 2009. To extend this study, we collected 3,234 adult mosquitoes of 16 species during 2009 and 2010 in the same sub-region. Mosquito pool homogenates were assayed for infectious virus on C6/36 and Vero cell monolayers and also tested for flaviviral RNA by a group-specific real-time RT-PCR. One pool containing 50 non-engorged female specimens of Aedes scapularis tested positive for ILHV by culture and for ILHV RNA by real-time RT-PCR, indicating a minimum infection rate of 2.5 per 1000. Full-length genomic sequence exhibited 95% identity to the only full genome sequence available for ILHV. The present data confirm the circulation of ILHV in the Brazilian Pantanal.